MO013: Relationship between Disease Awareness and Severity of Kidney Disease in Autosomal Dominant Polycystic Kidney Disease Patients. (3rd May 2022) - Dogan, Ege; Eren, Necmi; Gül Özcan, Şeyda; Altunoren, Orcun; Gungor, Ozkan; Dheir, Hamad; Tanrisev, Mehmet; Kocyigit, Hafsa; ülmecit Yıldız, Abd; Kocyigit, Ismail; Seyahi, Nurhan; Tatar, Erhan
Abstract: BACKGROUND AND AIMS: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease with diffuse cysts in both kidneys and is responsible for 5–10% of end-stage renal disease Levy and Feingold (Estimating prevalence in single-gene kidney diseases progressing to renal failure. Kidney Int . 2000;58(3):925). Recently, tolvaptan, which can improve kidney survival, was approved for the management of the disease (Drug Approval Package: Jynarque (tolvaptan) Otsuka Pharmaceutical Development & Commercialization, Inc. application Number: 204 441, Approval Date: 04/23/2018). We examined the relationship between renal and extrarenal findings, disease severity and the level of consciousness of patients with ADPKD patients. METHOD: About 516 patients who applied to nephrology clinics of seven different centers in Turkey were asked to answer the questionnaire about ADPKD that consisted of 38 questions. Disease severity was determined according to e-GFR, and disease awareness was assessed on a four-point scale by adapting the Disease Perception Scale to ADPKD. Awareness of patients was evaluated comparatively with chronic kidney disease stage, age, region and symptoms. RESULTS: One out of five patients does not know that this disease is inherited. Mean awareness scores of the patients decreased significantly with increasing age. The average awareness score of the Central Anatolia region was significantly higher compared to other regions. Awareness scores were significantly higher in patients with flank pain and urinary tract stones. CONCLUSION: To the best of our knowledge, this is the first study about ADPKD awareness. Although ADPKD is the most common hereditary kidney disease, the rate of patients' knowledge on this subject is low. Awareness levels may vary according to age, regional differences or symptoms. Increased awareness might lead to better treatment and improved survival in those patients.